2009
DOI: 10.1016/j.thromres.2008.11.016
|View full text |Cite
|
Sign up to set email alerts
|

The presence of γ′ chain impairs fibrin polymerization

Abstract: Introduction A fraction of fibrinogen molecules contain an alternatively spliced variant chain called γ’. Plasma levels of this variant have been associated with both myocardial infarction and venous thrombosis. Because clot structure has been associated with cardiovascular risk, we examined the effect of γ’ chain on clot structure. Materials and Methods We expressed three fibrinogen variants in Chinese hamster ovary (CHO) cells: γ/γ homodimer, γ/γ’ heterodimer, and γ’/γ’ homodimer. We observed thrombin-cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 32 publications
6
61
1
Order By: Relevance
“…Gersh et al synthesized all 3 fibrinogens recombinantly: ␥A/␥A homodimer, ␥A/␥Ј heterodimer, and ␥Ј/␥Ј homodimer. 76 In agreement with our study, 33 they found that the rate of thrombin-catalyzed FpA release was similar for all 3 variants, whereas FpB release from ␥Ј/␥Ј fibrinogen was faster than from either ␥A/␥Ј fibrinogen or ␥A/␥A fibrinogen. Fibrin polymerization studies suggested that the ␥Ј chain slowed lateral aggregation and reduced fiber diameter.…”
Section: Effect Of the Fibrinogen ␥ Chain On Fibrin Clot Structuresupporting
confidence: 89%
“…Gersh et al synthesized all 3 fibrinogens recombinantly: ␥A/␥A homodimer, ␥A/␥Ј heterodimer, and ␥Ј/␥Ј homodimer. 76 In agreement with our study, 33 they found that the rate of thrombin-catalyzed FpA release was similar for all 3 variants, whereas FpB release from ␥Ј/␥Ј fibrinogen was faster than from either ␥A/␥Ј fibrinogen or ␥A/␥A fibrinogen. Fibrin polymerization studies suggested that the ␥Ј chain slowed lateral aggregation and reduced fiber diameter.…”
Section: Effect Of the Fibrinogen ␥ Chain On Fibrin Clot Structuresupporting
confidence: 89%
“…Although previous work suggested that this difference reflects alterations in the structure of ␥Ј-Fn clots and/or enhanced stability because of increased FXIIIa-mediated crosslinking (6,10,11,16,17), we explored additional explanations. We show that (a) thrombinmediated release of FPB from ␥Ј-Fg is slower than that from ␥ A -Fg; (b) when ␥Ј-Fg is clotted with thrombin, but not with batroxobin, the rate of binding of Pg is reduced, and Pg activation is delayed; (c) when the Pg activation step is bypassed by using Pn in place of tPA and Pg, ␥Ј-Fn and ␥ A -Fn clots degrade at similar rates; and (d) with FXIIIa addition, degradation of ␥Ј-Fn and ␥ A -Fn clots is slowed to a similar extent.…”
Section: Discussionmentioning
confidence: 99%
“…The unique interaction of thrombin with ␥Ј-Fg not only attenuates the reactivity of the enzyme with its inhibitors, but also with its substrates, thereby reducing the activity and availability of thrombin. With less free thrombin, FPB release from ␥Ј-Fg is slower than that from ␥ A -Fg (6), which results in delayed clotting of ␥Ј-Fg relative to ␥ A -Fg (6,10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This effect on clot structure is caused by direct interference of the negatively charged ' extension with fibrin polymerisation and protofibril formation. Gersh et al showed increased ends or "capping" of ' fibers [13]. The ' fibers pack significantly less protofibrils and are less stiff than A fibers [14].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%